2007
DOI: 10.1371/journal.pone.0000950
|View full text |Cite
|
Sign up to set email alerts
|

Phylodynamics of HIV-1 in Lymphoid and Non-Lymphoid Tissues Reveals a Central Role for the Thymus in Emergence of CXCR4-Using Quasispecies

Abstract: BackgroundDuring HIV-1 infection coreceptor switch from CCR5- (R5)- to CXCR4 (X4)-using viruses is associated with disease progression. X4 strains of HIV-1 are highly cytopathic to immature thymocytes. Virtually no studies have evaluated the HIV-1 quasispecies present in vivo within thymic and lymphoid tissues or the evolutionary relationship between R5 and X4 viruses in tissues and peripheral blood.Methodology/Principal FindingsHigh-resolution phylodynamic analysis was applied to virus envelope quasispecies i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
45
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 47 publications
(49 citation statements)
references
References 77 publications
(84 reference statements)
4
45
0
Order By: Relevance
“…Such analysis has been used successfully to determine migration patterns of human immunodeficiency virus type 1 (HIV-1) and hepatitis C virus (HCV) within and between countries (Nakano et al, 2004;Salemi et al, 2008a, b) and to analyse the migration of HIV-1 between different compartments in the brain (Salemi et al, 2005) and between lymphoid and non-lymphoid tissues (Salemi et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such analysis has been used successfully to determine migration patterns of human immunodeficiency virus type 1 (HIV-1) and hepatitis C virus (HCV) within and between countries (Nakano et al, 2004;Salemi et al, 2008a, b) and to analyse the migration of HIV-1 between different compartments in the brain (Salemi et al, 2005) and between lymphoid and non-lymphoid tissues (Salemi et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…The worldwide migration of CCHFV was analysed by using a modified version of the Slatkin-Maddison test (Slatkin & Maddison, 1989), which counts migration events to and from subpopulations. Such analysis has been used successfully to determine the migration patterns of HIV-1 and HCV within and between countries (Nakano et al, 2004;Salemi et al, 2008a, b) and to analyse the migration of HIV-1 between different compartments in the brain (Salemi et al, 2005) and between lymphoid and nonlymphoid tissues (Salemi et al, 2007).…”
Section: Methodsmentioning
confidence: 99%
“…Examination of the tissue distribution of variants in the mouse in which the X4 virus emerged showed that 95% of variants in the MLN were X4 viruses, compared to 15% in the (82). In contrast, the MLN in wild-type mice is responsible for linking both inductive and effector sites of the gut-associated lymphoid tissue (GALT), such as Peyer's patches, the lamina propria, and mucosal epithelium.…”
Section: Discussionmentioning
confidence: 99%
“…env gp120 is exposed on the virus surface and is necessary for viral entry into lymphocytes (4). Neutralizing antibodies bind to env variable regions, exerting significant selection pressure on the protein (5,6). HIV-1 Nef, an accessory protein, is also required for the establishment and maintenance of infection in both humans and macaques (7)(8)(9).…”
mentioning
confidence: 99%